Language and Identity: An Inuit Perspective - Tulloch, Shelley (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2000)
The Inuit of Nunavut are calling for the protection, preservation and promotion of their language. At the root of these demands is the belief that their ancestral language is fundamentally linked to their culture and to their identity. Listening to the voices of Inuit who, faced with the threat of losing their language, express its fundamental importance, one gains new insight into the relationship between language and identity. This paper presents the voices of Inuit from Nunavut who were asked to speak about the significance of their language, and the link that they see between their language and their identity. Piercing the theoretical debate, these voices express the relationship between language and identity, as seen by those who may consider themselves at risk of losing both.